Improving Speaking Achievement of the Eleventh Grade Students of SMA Negeri 5 Palembang Through Time Token Arends - Visca Yulinda; Rita Hayati; Lingga Agustina (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2019)
This study was aimed to find out whether or not (1) there was a significant difference in speaking achievement before and after the students were taught through time token arends strategy, and (2) there was a significant difference in speaking achievement between the students who were taught through time token arends strategy and those who were not. The sample of this study was 60 eleventh grade students of SMA Negeri 5 Palembang which was chosen by using purposive sampling. It was divided into experimental and control groups, and each group had 30 students. To collect the data, pretest and posttest were given to the students. In scoring the students’ pretest and posttest, the writer used the rubric by Harris (1996). Then, the data were analyzed by using paired sample t-test and independent sample t-test in SPSS Version 24. The result of paired sample t-test showed that the p-value was lower than significance level (0.003<0.05). It means that there was a significant difference in speaking achievement before and after the students were taught through time token arends strategy. The result of independent sample t-test showed that the p-value was lower than significance level (0.006<0.05). It means that there was a significant difference in speaking achievement between the students who were taught through time token arends strategy and those who were not. In brief, time token arends strategy is helpful in enhancing students’ speaking achievement. Keywords: Improvement, Speaking Skill, Time Token Arends